Laporan Dua Kasus Sindrom Twiddler pada Pasien dengan Pemasangan Implanted Cardioverter-Defibrillator dan Permanent Pacemaker - Pipiet Wulandari; Sunu B Raharjo; Dicky A Hanafy; Lina Haryati; Yoga Yuniadi (The Indonesian Heart Association, 2017)
Background: Twiddler syndrome is an infrequent but potentially dangerous complication of device therapy for dysrhythmias. This syndrome results from manipulation of implanted pulse generator by the patient, leading to traction and subsequent lead dislodgement. It can also occur spontaneously. It has been increasingly reported with pacemaker or implantable cardioverter-defibrillators (ICDs). In this reports, we describe two patients with Twiddler syndrome with substantial retraction of their lead who denied any manipulation of their device.Case Illustration: The first patient was a 56 year-old man with single-chamber ICD due to dilated cardiomyopathy (DCM) with congestive heart failure and severe systolic left ventricular dysfunction (ejection fraction 18%). The dislodged lead causing rhythmical twitching of left pectoral muscles and abdominal pulsations. The second patient was a 69 year-old man with dual-chamber pacemaker due to total atrioventricular block with normal systolic left ventricular function (ejection fraction 70%). It manifested as dyspnea on effort, and he also underwent pacemaker implantation. They underwent primary devices implantation at April 2016 and reposition of generators and its leads in December 2016. The first and second patients denied of manipulating the generator of ICD or pacemaker and rotated their left arm and right arm, respectively, after implantation.Summary: Other unconscious arm abduction during sleep or increased muscular activity of the shoulder and arm might have led to repetitive motions within the pocket and dislodge the device. Adequate individualized patient and family education and regular evaluation every 6 month of the leads position with fluoroscopy or chest X-ray is advisable.